Dylan Thomas - Fraser, G. S. (George Sutherland), 1915-1980 (LiverpoolUniversity Press, 1972)
When Dylan Thomas died in New York in 1953 he was at the height of his fame. His Collected Poems had already enjoyed great success and he had shown exceptional gifts as broadcaster, entertainer, conversationalist and story-teller. Since his death, argument about his work has continued, and the response to Under Milk Wood has shown how alive general interest remains.